Who Should Undertake Corporate Social Responsibility in Freshness Preservation for Dual-Channel Fresh Food Products Supply Chain? - Rong Zhang; Lin, Rong (International Journal of Industrial Engineering: Theory, Applications and Practice, 2025)
This paper examines the impact of corporate social responsibility (CSR) on the fresh food supply chain. Using a Stackelberg game framework, three scenarios are developed: scenario M1(No CSR), scenario M2 (CSR by the retailer), and scenario M3 (CSR by the supplier), to make efforts on the freshness preservation. The analysis reveals that increased CSR commitment consistently leads to lower retail prices, more significant preservation efforts, and larger consumer surplus. While CSR enhances social utility, it often comes at the expense of supply chain members' profits. In the retailer-led CSR scenario, the supplier's dominant position increases overall supply chain profitability despite reduced retailer profits. Counter-intuitively, in the supplier-led CSR scenario, overall profitability decreases, but consumers benefit from fresher products at lower prices due to higher preservation efforts and lower online channel sales prices. The findings suggest that strategic CSR adoption can improve social welfare and market competitiveness, providing a theoretical basis for real-world business decisions. Future research could explore optimal CSR allocation within the supply chain to balance profitability and social welfare.